Strategic Responses to Financial Crisis - Toh, Voon Sia (2011)
This study examines the Malaysian financial institutions’ responses to the Macroenvironment during both the 1997-98 Asian financial crisis and the 2007-09 US subprime financial crisis.Based on the findings, results show that these three Malaysian financial institutions handled both the 1997-98 Asian financial crisis and the 2008-09 US subprime financial crisis well.Despite instability in the macro-environment, these financial institutions took the opportunities in strengthening their competitiveness in the banking industry rather than responding defensively. Their business reformations had strengthened not only their business foundations profoundly; these banks also accelerated their business growth during the economic slowdown. These financial institutions play an important role to deal with inevitable macro-environment i.e. politic, economy, social, technology, legal and environment (PESTLE). Instead of recreating new systems, these banks build on of existing programmes to further strengthen their performances during economic meltdown. Many initiatives were adopted during both the financial crises such as strengthening the overall risk management, business process reengineering and through offering innovative customer services.